Developing BIPA Teaching Materials Containing East Java Culture, Indonesia - Susanto, Gatut; Muzaki , Helmi; Saddhono, Kundharu Saddhono; Ermanto (Research Journal in Advanced Humanities, 2024)
This study aims to produce Indonesian language teaching materials for foreign speakers (BIPA) with East Javanese culture that has the feasibility of being used in middle-level BIPA learning. This research was conducted in Malang, East Java in 2022. The procedure used is the ADDIE model. The results of the study show that the developed BIPA teaching materials have the following four characteristics. First, the contents of the BIPA teaching materials contain the art of Reog Ponorogo as one of the cultural icons of East Java. Second, this teaching material consists of five three study units with the unit themes (1) Geographical Location of Ponorogo Regency, (2) Reog Ponorogo Art History, (3) characterizations in Reog Ponorogo, (4) Reog Ponorogo Performance, and (5) controversy Reog Ponorogo. Third, each lesson unit is enriched with pictures or photos that represent the topics discussed in the lesson unit. Fourth, this teaching material is equipped with videos. Fifth, each study unit is equipped with receptive and productive Indonesian language skills exercises. Based on the due diligence conducted on BIPA practitioners and Reog cultural figures, the following three pieces of information were obtained. First, the suitability of language for intermediate level language proficiency was obtained with a score of 86. Second, the suitability of cultural content in teaching materials with culture (Reog Ponorogo art) scored 95. Third, the systematic structure of presentation was 85. Based on the assessment scores of the three feasibility aspects above, it can be concluded that the material teaching BIPA with East Javanese culture as a result of this development is very suitable for use in middle-level BIPA learning.